Konsep Diversi terhadap Anak sebagai Pelaku Tindak Pidana Narkotika di Masa Depan - Imam Subaweh Arifin; Pujiyono (Perspektif Hukum, 2020)
When looking at social reality today, the number of children as perpetrators of crime is still significant, especially children as perpetrators of narcotic crimes. This encourages a study to find out how the concept of diversion in the future as an alternative settlement of cases of children as narcotics offenders. The research method used is a normative approach, which is also complemented by a comparative juridical approach. The data used are secondary data consisting of primary legal material in the form of laws and regulations on narcotic crime and the juvenile justice system. It uses secondary licensed content in the way of literature related to narcotics misconduct by children. The results of the study concluded that "the concept of diversion towards children in the future must expel children from the criminal justice process, relating to the handling of children who abuse police narcotics as holders of discretionary authority should diversify through medical rehabilitation and social rehabilitation programs without having to be confronted with the judicial process criminal.